2020
DOI: 10.3390/ijerph17145206
|View full text |Cite
|
Sign up to set email alerts
|

Does Water, Waste, and Energy Consumption Influence Firm Performance? Panel Data Evidence from S&P 500 Information Technology Sector

Abstract: This paper aimed to investigate the impact of water, waste, and energy consumption on firm performance for a sample of enterprises that belong to the S&P 500 Information Technology sector over the period of 2009–2020. The quantitative framework covered both accounting (e.g., return on assets—ROA; return on common equity—ROE; return on capital—ROC; return on invested capital—ROIC) and market-based measures of performance (e.g., price-to-book value—PB), alongside firm and corporate governance specific variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 97 publications
1
5
0
2
Order By: Relevance
“…Fourth, we also observed a positive and significant effect of PECP on firm performance, which suggest that an increase in PECP results to an increase in firm performance. This finding is inline with past findings which denote that efficient energy usage in guise of eco-friendly energy consumption can result in eco-friendly energy consumption performance; and eco-friendly energy consumption is a determinant for greater business performance (Bunse et al [14]; Hassan [33]; Makridou et al [50]; Schulze et al [57]; Simionescu et al [59]; Zhang et al [70]). The present finding extends this line of research by providing additional evidence from a Turkish context using primary first-hand data.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Fourth, we also observed a positive and significant effect of PECP on firm performance, which suggest that an increase in PECP results to an increase in firm performance. This finding is inline with past findings which denote that efficient energy usage in guise of eco-friendly energy consumption can result in eco-friendly energy consumption performance; and eco-friendly energy consumption is a determinant for greater business performance (Bunse et al [14]; Hassan [33]; Makridou et al [50]; Schulze et al [57]; Simionescu et al [59]; Zhang et al [70]). The present finding extends this line of research by providing additional evidence from a Turkish context using primary first-hand data.…”
Section: Discussionsupporting
confidence: 90%
“…Efficient energy usage by OECD firms has been revealed to increase the performance of firms based on panel data (Hassan [33]). Simionescu et al ( [59]) found that energy performance does not have any influence on firm performance. Schulze et al ( [57]) revealed that PECP is an important KPI for firms, and research have examined the association between EMS and PECP but have ignored the economic outcomes with few exceptions (Makridou et al [50]).…”
Section: Pro-environmental Energy Consumption Performance and Firm Performancementioning
confidence: 99%
“…Interest repayment ability (C34) Earnings before interest and tax/interest expense (Agbeko et al, 2017) Shareholders C4 Profitability (C41) Net profit/net assets (Elias, 2004) Asset utilization efficiency (C42) Net operating income/average total assets (Simionescu et al, 2020) Growth of firm (C43) Net profit growth rate (Akram et al, 2020) Enterprise market value level (C44) Tobin Q = market value/total assets (Taylor et al, 2018) Capital accumulation rate (C45) Owners' equity at the end of the period/owners' equity at the beginning of the period (Alvarez, 2010) Governments C5 Tax payment level (C51) Tax paid minus tax refund (Lin, 2020) Absorb the employed population (C52) Number of employees (Sarfraz et al, 2020) Compliance with regulations (C53) Whether the company violates laws or regulations (No 1/Yes 0) (Reis & Molento, 2019) Publics C6 Participate in public welfare activities (C61) Enterprise donation amount/main business income (Chun, 2021) Governance of pollution tax (C62) Ln (Operating income/enterprise sewage charge) (Xue et al, 2015) Environmental protection investment level (C63)…”
Section: Employees C1mentioning
confidence: 99%
“…However, business strategies involving sustainable product disposal focused on the perspectives of policymakers and firms (Gonenc & Scholtens, 2017; Simionescu et al, 2020). For example.…”
Section: Background and Hypotheses Developmentmentioning
confidence: 99%